Du sol pour l’habitant au sol pour le vivant. L’histoire des traces génératrices de biodiversité dans le projet de recherche Morphobio Toulouse - Laura Girard; Constance Ringon; Anaïs Leger-Smith (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article studies the place of history in the framework of the MorphobioT research project. Through an analysis of five Toulouse neighborhoods (in France) with distinct origins (i.e. faubourg, company town “Castor”, large housing estate, suburban housing and eco-district), we review the current research in order to highlight the specific approaches of historians. Here, the investigation focuses on different urban fabrics and their capacity to host and maintain biodiversity in an urban environment. Historians’ tools are compared to those specific to other disciplines, paying attention to history’s contribution to research embedded in present-day questions: the place of living organisms in an urban environment.